MOFs-derived defect carbon encapsulated magnetic metallic Co nanoparticles capable of efficiently activating PMS to rapidly degrade dyes - Tan, Jianke; Xu, Chengji; Zhang, Xiaodan; Huang, Yuming (Separation and purification technology, 2022)
A new MOFs-derived defect carbon encapsulated magnetic metallic Co NPs (Co@DC) was fabricated via directly pyrolyzing Co-BTC MOFs, showing magnetism, abundant carbon defects, stable Co NPs and wide pH adaptability. The Co0 in the Co@DC took part in PMS activation to drive Co2+/Co3+ cycle to maintain high RhB removal. [Display omitted] •Simple synthesis of Co@DC via directly pyrolyzing Co-BTC MOFs at 900 °C.•Magnetic Co@DC features abundant defects, stable Co NPs, and wide pH adapbility.•The Co@DC exhibits 17 times higher RhB degradation rate constant than C-900.•Co0 took part in PMS activation to drive Co2+/Co3+ cycle to keep high RhB removal. In this work, a new defect carbon encapsulated magnetic metallic Co nanoparticles (denoted as Co@DC) was prepared via pyrolyzing Co-BTC (BTC: 1,3,5-trimesic acid) MOFs precursor at 900 °C, and characterized by various technologies to prove that the Co@DC contains Co0, Co2+ and Co3+. It was used to activate peroxymonosulfate (PMS) to degrade Rhodamine B (RhB) dye efficiently. Over 99% of 10 mg/L RhB with initial pH of 5.5 was degraded by 100 mg/L PMS activated by 10 mg/L Co@DC within 5 min. The RhB degradation rate constant in the Co@DC/PMS system was 1.1805 min−1, which was approximately 17 times that of DC/PMS system (0.0695 min−1). The Co@DC displayed a good magnetism, stability, and PMS activation ability in a wide pH range of 3 to 10. After four cycles, the RhB removal rate can still maintain over 90% after 10 min reaction. The Co@DC/PMS system can also rapidly degrade the other dyes (acid fuchsin, methylene blueandmethyl orange), showing excellent universality. The free radical quenching experiments and EPR trials suggest that both the radicals (sulfate radical, hydroxyl radical, and O2•−) and non-radical (singlet oxygen) species are involved in the RhB degradation, while the latter plays a major role. In addition to the cobalt ions, the metallic Co0 also took part in PMS activation and reacted with O2 to generate Co2+, ensuring the sufficient Co2+ to activate the PMS to produce Co3+. The Co3+ ions withdraw electrons from HSO5− or Co0 in the Co@DC catalyst, driving a Co2+/Co3+ cycle to maintain a high performance of the Co@DC/PMS system for RhB removal. The effects of common inorganic anions on RhB removal, the mineralization degree and possible degradation pathway of RhB were studied. Relative to the previous catalysts for PMS activation to degrade RhB, the Co@DC shows lower activation energy of 23.78 KJ/mol. Altogether, this work provides a simple strategy to develop an efficiently magnetic heterogeneous catalyst to activate PMS for the elimination of hardly degradable dyes.